1980
DOI: 10.1111/j.1469-7998.1980.tb01475.x
|View full text |Cite
|
Sign up to set email alerts
|

Static allometry of mammalian teeth and the correlation of tooth size and body size in contemporary mammals

Abstract: Functional least squares regression was used to fit the allometric equation, y= bxk, to data on head‐body lengths and body weights for 123 species of mammals. These measurements were found to be highly correlated and to scale isometrically. The scaling of M1 area with head‐body length was investigated for 288 species of terrestrial mammals. A method was described for estimating the body size of extinct mammals from M1 area and the tooth size‐body size relationships discovered among contemporary forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

1982
1982
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(22 citation statements)
references
References 12 publications
2
17
0
2
Order By: Relevance
“…These values are similar to previous estimates based on head-body length (9 kg and 32 kg, respectively; Van Valkenburgh 1987) and limb bone dimensions (10-25 kg and 25-60 kg; Egi 2001), but much lower than reconstructions based on the length of the skull (23 kg and 150 kg; Van Valkenburgh 1987). Because head-body length is considered to be a reliable predictor of body mass (Creighton 1980;Damuth 1990;Van Valkenburgh 1990), these comparisons may indicate that the astragalus performs well in estimating the body mass of hyaenodontids.…”
Section: Application To Paleogene Mammalssupporting
confidence: 77%
“…These values are similar to previous estimates based on head-body length (9 kg and 32 kg, respectively; Van Valkenburgh 1987) and limb bone dimensions (10-25 kg and 25-60 kg; Egi 2001), but much lower than reconstructions based on the length of the skull (23 kg and 150 kg; Van Valkenburgh 1987). Because head-body length is considered to be a reliable predictor of body mass (Creighton 1980;Damuth 1990;Van Valkenburgh 1990), these comparisons may indicate that the astragalus performs well in estimating the body mass of hyaenodontids.…”
Section: Application To Paleogene Mammalssupporting
confidence: 77%
“…In mammals, skull and body parameters are related. For example, Creighton (1980) showed that tooth size of 123 species of mammals was significantly related to body size, and Johnston (1991) showed that, in the weasel Mustela frenata, cranial length and mass, as well as zygomatic breadth, were significantly related to body size.…”
Section: Methodsmentioning
confidence: 97%
“…Using digital calipers, four measurements were taken from each skull to an accuracy of 0.01 mm: greatest length (GTL) from the front of the premaxilla above the incisors to the back of the lamboidal crest, the maximal width of the zygomatic breadth (ZB), the minimal width of the interorbital constriction (IO) and antero-posterior diameter of the upper canine. In mammals, the three skull parameters (GTL, ZB and IO) are correlated with body weight and length (Creighton 1980;Johnston 1991), and in felids the size of the canine is generally associated with prey size (Ewer 1973). We also used principal component analysis (PCA) to combine the information of the three skull measurements (GTL, ZB and IO) into a single variable.…”
Section: Methodsmentioning
confidence: 99%